The Analisis Retrospektif Penerapan Metode Long Interval Training dengan MAS Tinggi Terhadap Kapasitas Speed Endurance - Nizrina Fauziah Permana; Dikdik Zafar Sidik; Patriana Nurmansyah Awwaludin; Fitri Rosdiana (Universitas Hamzanwadi, 2026)
Futsal requires speed endurance to maintain speed during repeated sprints, accelerations, and changes of direction at high intensity. Long Interval Training (LIT) based on high Maximum Aerobic Speed (MAS) is often used to develop aerobic and anaerobic capacity, but its effectiveness for speed endurance still needs further study. This study aims to retrospectively analyze the application of the Long Interval Training method with high MAS on the speed endurance capacity of female futsal athletes. The study used a quantitative approach with an ex post facto method and a retrospective design. The subjects consisted of 4 female futsal athletes from the UPI Student Club, selected purposively based on the completeness of their pretest and posttest data for the 150-meter sprint and their MAS rankings within the entire population. Data analysis utilized descriptive statistics and the Shapiro-Wilk normality test. The average 150-meter sprint time increased from 24.30 seconds in the pretest to 26.38 seconds in the posttest, with an average difference of 2.08 seconds (8.44%). All athletes experienced a slowdown in their completion times, with three athletes experiencing a decline in performance category from moderate/poor to very poor. The implementation of Long Interval Training with high MAS has not yet shown an optimal improvement in speed endurance capacity among female futsal athletes. Future training programs need to combine LIT with specific speed endurance training, such as repeated sprints.